Determination of the phase instability parameters for penton – AgI system - Rokitskaya, Galina V.; Shut, Nikolay I.; Rokitskiy, Maksim A. (Journal of the Belarusian State University. Physics, 2017)
The studying of interaction between the components of polymer composite materials (PCM) – is one of the fundamental complex and multifaceted problems of polymer physics. Perspective to identify internal stresses between PCM components are the systems with dispersed fillers which are characterized by phase transitions and abnormal dilatometric behavior. A good representative of fillers with such properties is silver iodide. In this research the temperature dependences of the specific heat of penton – silver iodide (AgI) system have been studied. The bimodal cp = f(T) dependences in the phase instability region of the composite components have been subdivided into their constituents. The parameters of endothermic processes have been determined; the physical interaction magnitude of the system components has been estimated.